Registered nurses’ experiences regarding clinical virtual learning during COVID-19 in Gauteng - Simelane, Neliswa L.; Sepeng, Nombulelo V.; Mashao, Kapari (Health SA = SA Gesondheid, 2025)
Background: Virtual clinical learning variedly impacted newly registered nurses’ confidence. For some, it led to a lack of confidence in performing specific procedures, while for others, effective virtual learning fostered a high confidence level. This dynamic is likely to be even more complex when newly qualified nurses transition from education to practice, as healthcare facilities have high expectations, anticipating a certain level of knowledge and competence despite the challenges posed by coronavirus disease 2019 (COVID-19). Aim: The study explored newly registered nurses’ virtual experiences of learning clinical skills during COVID-19 and its impact on their transition into professional practice in the Tshwane District of Gauteng province in South Africa. Setting: The study was conducted in two selected hospitals in the Tshwane District of Gauteng province. Methods: Using unstructured interviews, a qualitative exploratory, descriptive and contextual design was executed to collect data. Purposive and snowballing sampling were utilised to reach to the sample of 12 registered nurses. Results: Three themes emerged in this study, namely: (1) Impact of virtual learning on confidence in clinical practice, (2) Challenges of transitioning from virtual learning to practical application and (3) Recommendations for enhancing virtual learning in nursing education. Conclusion: The study revealed both potential benefits and drawbacks of virtual clinical teaching on registered nurses’ transition into professional practice. Contribution: The findings may guide strategies to help nursing education institutions design virtual learning that ensures competent, practice ready nurses.